Life History of Cochliomyia macellaria (Fabricius, 1775) (Diptera, Calliphoridae), a Blowfly of Medical and Forensic Importance (2017)
The life history traits of blow fly Cochliomyia macellaria (Fabricius, 1775) was studied under semi-controlled laboratory conditions at 29.14°C temperature, 72.53% relative humidity, and 12-h photoperiod. The raw data were analyzed based on the age-stage, two-sex life table, considering the development rates among individuals of both sexes. Cochliomyia macellaria survival rate was 0.43 (♂) and 0.40 (♀), while life expectancy was 17.9 (♂) and 20.9 (♀) days, for adult males and females, respectively. The total fecundity was 681.15 eggs/female, with an average of 3.65 batches/female and 199 eggs/batch. The intrinsic rate of increase (r) was 0.327 days−1, the finite rate of population increase (λ) was 3.35 days−1, the mean generation time (T) was 17.15 days, and the net reproduction rate (R 0 ) was 272.46 offspring/individual. The population parameters found here corroborates that C. macellaria population act as a r selected species under laboratory conditions. Additionally, development data and accumulated degree days (ADD) for each stage of C. macellaria are provided and its implications for the forensic use are discussed.